Brief Report: Gonorrhea and Chlamydia Testing Increasing but Still Lagging in HIV Clinics in the United States. (1st November 2015) - Berry, Stephen A.; Ghanem, Khalil G.; Mathews, William Christopher; Korthuis, Philip Todd; Yehia, Baligh R.; Agwu, Allison L.; Lehmann, Christoph U.; Moore, Richard D.; Allen, Sara L.; Gebo, Kelly A.
Abstract : Abstract: Screening persons living with HIV for gonorrhea and chlamydia has been recommended since 2003. We compared annual gonorrhea/chlamydia testing to syphilis and lipid testing among 19, 368 adults (41% men who have sex with men, 30% heterosexual men, and 29% women) engaged in HIV care. In 2004, 22%, 62%, and 70% of all patients were tested for gonorrhea/chlamydia, syphilis, and lipid levels, respectively. Despite increasing steadily [odds ratio per year (95% confidence interval): 1.14 (1.13 to 1.15)], gonorrhea/chlamydia testing in 2010 remained lower than syphilis and lipid testing (39%, 77%, 76%, respectively). Interventions to improve gonorrhea/chlamydia screening are needed. A more targeted screening approach may be warranted. Abstract : Supplemental Digital Content is Available in the Text.